“Aplicación de técnicas de enseñanza para el aprendizaje de la destreza oral en los niños del Primer Año de Educación General Básica, de la Escuela de Educación Básica Fiscomisional ‘Dr. Gabriel García Moreno’ del Cantón Guano, Provincia de Chimborazo; durante el año lectivo 2013-2014”. - Vargas Vimos, Amparo Isabel (2014)
This study considers the importance of English qualified at present as the world’s “Lingua Franca” and childhood as the best time to start learning another language. It proposes the application of techniques based on: active learning, multisensory teaching and interactive techniques which promote the development of the oral skill of English language and are applicable to students of Primer Año de Educación Básica. The techniques are: Choral responses, total physical response (TPR), pass the ball, drawing for understanding and simulation and are combined with some principles of communicative approach and task based learning method. After the application the 100% of students have developed the speaking skill; some more than others but at difference from the beginning, all of them speak some basic English phrases and try and want to continue practicing. At the same time it is noticed that the teacher uses more English while teaching the language, the students are more interested on the subject, motivated, participative and it is noticeable that the they understand most of what the teacher says, because of the interaction and the flow of the class; so, It can be assured that the teaching techniques proposed influences positively on the oral skill development in the students of Primer Año de Educación General Básica, at Escuela de Educación Básica Fiscomisional ‘Dr. Gabriel García Moreno’.